Enhancing Vocational Students' Critical Thinking Skills in Society 5.0 with Flipbook and Augmented Reality Learning Media - Sabitri, Zenita; Meirawan, Danny; Rahayu, Sri (invotek, 2024)
The era of Society 5.0 demands that human resources possess critical thinking skills in response to rapid changes in the field of education, with Vocational High Schools (VHS) playing a central role in shaping students to be critical and creative. To achieve optimal results, further breakthroughs in the use of educational technology are needed, such as the implementation of Augmented Reality (AR)-based flipbooks in the vocational school environment. This study aims to evaluate the level of critical thinking skills among vocational school students. The method used in this study is a quasi-experimental design with descriptive quantitative data analysis. This research was conducted with 64 tenth-grade students at a vocational school in Bandung. The instruments used to obtain data included critical thinking skills tests. The data analysis technique used was descriptive quantitative analysis to evaluate the improvement of students' understanding and critical thinking skills. The research data was tested using normality test, homogeneity test, independent test, and N-Gain. Research data indicates that the use of AR-based flipbooks significantly enhances student comprehension, with an N-gain value of 0.6 observed in the experimental class. Consequently, it can be concluded that the implementation of AR-based flipbooks effectively improves students' critical thinking abilities in VHS, offering substantial promise for developing more interactive and efficient learning technologies for future education.